Identification of necroptosis-related subtypes, development of a novel signature, and characterization of immune infiltration in colorectal cancer - Sun, Mengyu; Ji, Xiaoyu; Xie, Meng; Chen, Xiaoping; Zhang, Bixiang; Luo, Xiangyuan; Feng, Yangyang; Liu, Danfei; Wang, Yijun; Li, Yiwei; Liu, Bifeng; Xia, Limin; et al. (Frontiers in Immunology, 2022)
Necroptosis, a type of programmed cell death, has recently been extensively studied as an important pathway regulating tumor development, metastasis, and immunity. However, the expression patterns of necroptosis-related genes (NRGs) in colorectal cancer (CRC) and their potential roles in the tumor microenvironment (TME) have not been elucidated. We explored the expression patterns of NRGs in 1247 colorectal cancer samples from genetics and transcriptional perspective. Based on a consensus clustering algorithm, we identified two NRG molecular subtypes and two gene subtypes, respectively. We found that distinct subtypes exhibited different NRGs expression, patients’ prognosis, immune infiltration characteristics in TME, and immune checkpoint gene expression. Furthermore, we constructed a necroptosis-related signature for predicting overall survival time and verified the predictive ability of the model. The scores calculated from the signature can be used to classify patients into high-risk and low-risk groups, with the high-risk group corresponding to reduced immune cell infiltration and immune function, and a greater risk of immune dysfunction and immune escape. Our comprehensive analysis of NRGs in CRC demonstrated their potential role in clinicopathological features, prognosis, and immune infiltration in the TME. These findings help us deepen our understanding of NRGs and the tumor microenvironment landscape, and lay a foundation for effectively assessing patient outcomes and promoting more efficient immunotherapy.